Capital Punishment in Brazil: Exploring Factors That Predict Public Support for the Death Penalty. (February 2022) - Boateng, Francis Danso; Dzordzormenyoh, Michael K.
The primary purpose of this study was to examine public support for the death penalty in Brazil and to determine factors that influence such support. Currently, Brazil has the death penalty for cases involving war crimes, genocides, terrorism, and crime against humanity. The country's constitution, however, prohibits the use of the death penalty in ordinary crimes. Analyzing individual-level cross-sectional data collected by the American Barometer Survey, we found that a significant majority of Brazilians support the death penalty, with more than two thirds expressing greater support. In terms of factors, it was revealed that frequency of murders, sense of insecurity, and perceived institutional legitimacy largely influence support for the death penalty. In addition, ethnicity, religiosity, and religious affiliation affect citizens' attitudes toward the death penalty. The findings of this study have serious implications for research and practice.